Hábitos alimenticios y físicos en relación con el estado nutricional en niños y niñas de la escuela González Suárez de la parroquia Chuquiribamba en el periodo enero-junio 2013 - Satama Caraguay, María Isabel (2014)
The thesis about nutritional and physic habits and its relationship with nutritional state on male and female children of La Escuela González Suárez from Chuquiribamba parish, during January – June 2013; it was carried out in this parish from the Loja Canton. The whole universe of 120 people, constituted the sample for this research. The main objective stablished was: To analyze the nutritional and physic habits and its relationship with nutritional state on male and female children from la Escuela González Suárez from Chuquiribamba parish during January – June 2013; and the specific objectives were: To know the nutritional habits, to identify if the male and female children practice some physical activity and to determine the nutritional state of the male and female children through anthropometric data. The Index of bodily Mass/age (IBM/A) was used and it was completed with a survey application about nutritional habits and some physical activities to the children’s representatives. This conclude that most children are eutrophic with 62.50%; the 27.34% are wasted and 10.16% are overweight. Analyzing eating habits 62.5% had inadequate food, and 37.5% have adequate food. With regard to physical activity 43% not performed, 12.5% sometimes and 44.5% performed daily. As for the relationship of food habits to nutritional status, it can be concluded that children with adequate food are eutrophic 31.25%, 1.56% and 4.69% wasted overweight. Of the population have inadequate dietary habits are eutrophic 31.25%, 25.78% the emaciated and 5.47% are overweight. From the relationship between exercise habits and nutritional status, it is concluded that the 31.30% of the population who are not physically active are eutrophic, 3.90% and 7.80% wasted overweight. Children who engage in physical activity at times the 6.30% are eutrophic, wasted 3.90% and 2.30% are overweight. Of the population takes daily physical activity 19.5% are wasted and 25% are eutrophic. Keywords: Eating Habits, Nutritional Status, Physical Activity, BMI